Behavior of Pertamini Retail Gasoline Traders After the Existence of Public Fuel Filling Stations (SPBU) (International Journal of Education and Literature, 2025)
This research was conducted with the aim of describing the behavior and outlining the strategies implemented by Pertamini retail gasoline traders in maintaining their businesses after the establishment of a gas station in Umbulan Village. The use of methods in this research is descriptive qualitative research with data collection techniques through observation, in-depth interviews, and documentation. In this study, it was found that the behavior of Pertamini retail gasoline traders after the establishment of a gas station in Umbulan Village is more dominantly influenced by external factors from the surrounding environment or market conditions such as the gas station's operating hours, the shift of customers to the gas station, and the proximity to the gas station in Umbulan Village. Thus, the Pertamini retail gasoline traders demonstrate resilience by adapting to market changes and remaining focused on their main objectives, as reflected in their commitment to keep their business open every day despite having few customers. Traders also build close relationships with local customers and suppliers, which are not only based on economic transactions but also on social relations. Although there are disputes between the retail gasoline traders and the Umbulan Village gas station, the traders strive to maintain good relationships. Then, the traders maintain their relationship patterns through good communication and close social interactions, which highlight the importance of social norms in maintaining harmonious relationships. By implementing adaptation strategies, achieving goals, integration, and maintaining good relationship patterns, they strive to survive in the increasingly fierce competition.